2012
DOI: 10.1142/s0218625x12500357
|View full text |Cite
|
Sign up to set email alerts
|

H2 INTERACTION WITH BIMETALLIC DIMERS SUPPORTED ON THE MgO(100) SURFACE: A DFT CLUSTER MODEL STUDY

Abstract: The interaction between the H 2 molecule and the PdAg, PdAu, PtAg and PtAu bimetallic dimers deposited on the MgO(100) surface is investigated using density functional theory (DFT). The bimetallic dimers, whose molecular axes are considered to be perpendicular to the support surface, are adsorbed on top of an oxygen atom. Within this adsorption mode, the dimers prefer the orientation in which their Pd or Pt end is closer to the oxygen atom. The Ag and Au ends of the MgO-supported dimers capture the H 2 molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The knowledge gained from this kind of studies could allow us to optimize the chemical reactivity of clusters by the adjustment of the chemical composition. [21][22][23][24] For example, Matczak investigated H 2 interaction with MgO(001) supported PdAg, PdAu, PtAg and PtAu bimetallic dimers and showed that MgO support decreases the ability of the dimers to adsorb and dissociate hydrogen molecules. 21 Florez et al investigated Cu n M (M = Ni, Pd, Pt; n = 1 to 4) bimetallic nanoparticles adsorbed on the F s center of MgO(001) and showed that chemical reactivity depends on the nanoparticle arrangement on the surface as well as on the type of binding atom (Cu or M).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge gained from this kind of studies could allow us to optimize the chemical reactivity of clusters by the adjustment of the chemical composition. [21][22][23][24] For example, Matczak investigated H 2 interaction with MgO(001) supported PdAg, PdAu, PtAg and PtAu bimetallic dimers and showed that MgO support decreases the ability of the dimers to adsorb and dissociate hydrogen molecules. 21 Florez et al investigated Cu n M (M = Ni, Pd, Pt; n = 1 to 4) bimetallic nanoparticles adsorbed on the F s center of MgO(001) and showed that chemical reactivity depends on the nanoparticle arrangement on the surface as well as on the type of binding atom (Cu or M).…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] For example, Matczak investigated H 2 interaction with MgO(001) supported PdAg, PdAu, PtAg and PtAu bimetallic dimers and showed that MgO support decreases the ability of the dimers to adsorb and dissociate hydrogen molecules. 21 Florez et al investigated Cu n M (M = Ni, Pd, Pt; n = 1 to 4) bimetallic nanoparticles adsorbed on the F s center of MgO(001) and showed that chemical reactivity depends on the nanoparticle arrangement on the surface as well as on the type of binding atom (Cu or M). 22 Obviously, catalysis via highly undercoordinated metal atoms becomes a reality, but very little is known about the electronic structure parameters that govern their reactivity.…”
Section: Introductionmentioning
confidence: 99%